Improving the thermal and mechanical properties of phenolic fiber over boron modified high-ortho phenolic resin. (June 2021) - Ren, Yu; Lin, Xu; Shi, Zhengjun; Zheng, Yunwu; Liu, Jianxiang; Zheng, Zhifeng; Liu, Can
Boron-modified high-ortho phenolic resins (BPRs) were prepared under normal pressure by using phenol and formaldehyde as raw materials, zinc acetate, and oxalic acid as catalysts, and boric acid as a modifier. Boron-modified phenolic fibers (BPFs) were prepared by melt spinning and curing in a mixture of formaldehyde and hydrochloric acid, followed by a heat treatment under high temperature. The structure, ortho–para ratio (O/P), molecular weight and distribution, spinnability, thermal stability, fiber strength, and morphology of the resins were characterized by Fourier transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR), gel permeation chromatography (GPC), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and fiber strength testing. The results showed that the addition of boric acid reduced the ortho reaction of the synthetic resin and the O/P value of phenolic resin. When the content of boric acid was 3 wt%, the thermal stability was the best, the O/P value was up to 3.26, and the weight average molecular weight (Mw) was 18745 g/mol. In Compared with the unmodified resin, the mass loss was increased by 33.7%, and finally the carbon yield was 51.2%. The tensile strength of the fibers reached 187.2 MPa and the elongation at break was 10.5%. By introducing boron into the molecular chain, the structure of the resin was improved, and the thermal stability and mechanical properties of the fibers were improved.